America's boy - Hamilton-Paterson, James (Pasig City : Anvil Pub, 1998)
Cover title: The Marcos and the Philippines
Includes references and index.
Keywords: Marcos, Ferdinand Edralin, Pres., Philippines, 1917-1989; Philippines -- Politics and government -- 1965-1985